'Post‐LA space index' as a potential novel marker for the prenatal diagnosis of isolated total anomalous pulmonary venous connection. (30th October 2014) - Kawazu, Y.; Inamura, N.; Shiono, N.; Kanagawa, N.; Narita, J.; Hamamichi, Y.; Kayatani, F.
ABSTRACT Objectives To review the fetal echocardiograms of patients with total anomalous pulmonary venous connection (TAPVC) in order to determine whether the distance between the left atrium and the descending aorta would be useful in the prenatal diagnosis of fetal TAPVC. Methods We reviewed the fetal echocardiograms of eight cases of TAPVC (five supracardiac type and three infracardiac type) with no other cardiac malformations. We evaluated the ratio of the left atrium–descending aorta distance to the diameter of the descending aorta ('post‐LA space index') in 101 normal and eight TAPVC fetuses, and compared the values between groups. In addition, we examined the tricuspid valve/mitral valve diameter ratio (TVD/MVD) and the right ventricular end‐diastolic diameter/left ventricular end‐diastolic diameter ratio (RVDd/LVDd). Results The echocardiograms for fetuses with TAPVC and normal fetuses were performed at mean gestational ages of 27.5 weeks and 29.6 weeks, respectively. There were no significant differences in the TVD/MVD and RVDd/LVDd ratios between the groups. However, the post‐LA space index was significantly higher in the TAPVC cases (mean, 1.51) than it was in the normal fetuses (mean, 0.71 ± 0.23) (P < 0.0001). On an analysis of the receiver–operating characteristics curve, a post‐LA space index cut‐off of 1.27 was found to be optimal for distinguishing between TAPVC and normal hearts, with a sensitivity of 100% and specificity of 99%. Conclusions The novel post‐LA space index could potentially be used for the prenatal diagnosis of TAPVC. A diagnosis of TAPVC is very likely in cases with a post‐LA space index of > 1.27. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.